Whirl flutter of turboprop aircraft structures - Cecrdle, Jiri (Woodhead Publishing in mechanical engineering., 2015)
Whirl flutter is the aeroelastic phenomenon caused by the coupling of aircraft propeller aerodynamic forces and the gyroscopic forces of the rotating masses (propeller, gas turbine engine rotor). It may occur on the turboprop, tilt-prop-rotor or rotorcraft aircraft structures. Whirl Flutter of Turboprop Aircraft Structures explores the whirl flutter phenomenon, including theoretical and practical as well as analytical and experimental aspects of the matter. The first introductory part gives a general overview regarding aeroelasticity, followed by the physical principle and the occurrence of whirl flutter in aerospace practice. The next section deals with experiment research including earlier activities performed, particularly from the sixties, as well as recent developments. Subsequent chapters discuss analytical methods such as basic and advanced linear models, and non-linear and CFD based methods. Remaining chapters summarize certification issues including regulation requirements, a description of possible certification approaches and several examples of aircraft certification from the aerospace practice. Finally, a database of relevant books and reports is provided.